Pemenuhan Hak Anak Pasca Perceraian Orang Tua - Nyoto Nyoto; Budi Kisworo; Rifanto bin Ridwan; Hasep Saputra (IAI Darussalam, 2020)
This study aims to determine the fulfillment of children's rights after parental divorce in Rejang Lebong Regency. Knowing the obstacles experienced by parents so that they cannot fulfill their children's rights after divorce. This is to find out the implications of not fulfilling children's rights after parents' divorce on children's lives. This study uses a qualitative method to describe the fulfillment of children's rights after their parents' divorce. Barriers experienced by parents in fulfilling children's rights. As well as the implications of not fulfilling the rights of children. The results show that the responsibility of parents is not only concerned with the child's growth and development but also with the physical health of the child itself, the obligations and responsibilities of parents towards the child, at this time, that divorced parents have the responsibility to regulate the obligations towards the child. post-divorce child. Starting from the arrangement of child custody, child support so that no problems arise after the divorce between parents